Analysis of Transfer Pricing Policy Disclosure: Case Study of PT. Mandom Indonesia Tbk for the 2020–2024 Period - Nugroho, Agung Rizky; Dewi, Siti Ratna Sari (Manunggal Halim Jaya, 2026)
This study analyzes the disclosure of transfer pricing policies in the financial statements of PT Mandom Indonesia Tbk for the period 2020–2024 and evaluates their compliance with PSAK No. 7 and Indonesian tax regulations, particularly the transition from PMK 213/PMK.03/2016 to PMK 172/PMK.03/2023. Using a qualitative descriptive approach with a case study method, the research relies on secondary data obtained from annual financial statements and local transfer pricing documentation. The findings reveal that PT Mandom Indonesia Tbk consistently complies with formal disclosure requirements, presenting information on related parties, transaction types, amounts, and ending balances in line with PSAK No. 7. However, a substantive compliance gap remains evident, as the transfer pricing methods (e.g., CUP or TNMM) are not explicitly disclosed in the Notes to the Financial Statements (CaLK), thereby limiting transparency as required under PMK 172/PMK.03/2023. Furthermore, the Country-by-Country Report (CbCR) is not yet publicly available, and inconsistencies persist between financial statement disclosures and local documentation. Consequently, PTMI’s compliance appears administrative rather than substantive, as it has not fully satisfied the arm’s length principle and the economic justification emphasized in PMK 172/PMK.03/2023. The study contributes to accounting and taxation literature by offering a framework for improving transfer pricing disclosures that balance formal compliance with substantive transparency, thereby enhancing governance credibility and stakeholder confidence.